Serum procalcitonin concentrations in transplant patients with acute rejection and bacterial infections - Jaresová, M; Stríz, I; Cermáková, J; Lácha, J; Sedlácek, J; Mudra, K; Hána, I; Vítko, S (Immunology letters, 1999)
Procalcitonin (PCT) represents a new marker of systemic inflammatory reactions of the body to infections. PCT is selectively induced by severe bacterial infections leading to sepsis or multiorgan dysfunction syndrome. The aim of our study was to test PCT as a postoperative infection marker in heart and kidney transplant patients compared with healthy subjects and patients with localized lung-inflammatory processes without a manifest systemic response. PCT concentrations were measured by an immunoluminometric assay (ILMA) in a total of 419 serum samples. Normal serum levels were in the range of 0.08-0.6 ng/ml. Operative trauma associated with heart (not kidney) transplantation induced a transient increase in PCT levels to 7-10 ng/ml with a decline to normal levels within 2-3 days in most patients. Severe bacterial infections dramatically augmented serum PCT concentrations reaching values of 46-297 ng/ml in the most critical periods. Good response to antibiotic therapy was associated with a decline in serum PCT concentrations. Acute rejection or cytomegalovirus infections did not significantly increase the serum PCT levels. Localized pulmonary infections showed either no, or only a limited increase, in the serum PCT levels (max. 7 ng/ml). We conclude from our data that PCT can be used as a sensitive marker to differentiate systemic bacterial infections from other complications in organ transplantation.
Keywords: rejekce štěpu; transplantace srdce; Calcitonin; Kidney Transplantation; Heart Transplantation; bakteriální infekce; Calcitonin Gene-Related Peptide; Bacterial Infections; Protein Precursors; biologické markery; lidé; peptid spojený s genem pro kalcitonin; proteinové prekurzory; Graft Rejection; transplantace ledvin; Biomarkers; Humans; kalcitonin